Karakteristik Unsur Jejak Dalam Diskriminasi Magmatisme Granitoid Pulau Bangka - Widana, Kurnia Setiawan; Priadi, Bambang (BRIN Publishing, 2015)
Geology of Bangka Island consists by variation of granite as Klabat Granitoid scattered in various locations. Trace elements can be applied in magmatism discrimination of granitoid.The purpose of this study was to determine the characteristics Bangka Island granitoid based on trace element geochemistry to be applied in the study of magmatism, source and tectonic situation. Geochemical analyses method used are the Neutron Activation Analysis (NAA) and portableX-Ray Fluorescence (pXRF) for qualitative and quantitative analyses on 27 samples of Klabat granitoid on Bangka Island. This study concluded granitoid East Bangka (Belinyu) and Central Bangka as crust-mantle mixing with affinityCalc-Alkaline, characteristic of I Type while South and West Bangka granitoid crust origin with affinity high K Calc-Alkaline as S Type. Expectedmagmatismdiscrimination ofgranitoidhelpfulin providingradioactive mineral explorationguidein BangkaIsland.